Preparation, Characterization, and Analytical Application of Ramipril Membrane-Based Ion-Selective Electrode - Hassan Arida; Mona Ahmed; Abdallah Ali (International Journal of Analytical Chemistry)
The fabrication and electrochemical evaluation of two PVC membrane-based Ion-Selective electrodes responsive for ramipril drug have been proposed. The sensitive membranes were prepared using ramipril-phosphomolibdate and ramipril-tetraphenylborate ion-pair complexes as electroactive sensing materials in plasticized PVC support. The electrodes based on these materials provide near-Nernestian response (sensitivity of 53±0.5–54±0.5 mV/concentration decade) covering the concentration range of 1.0×10-2–1.0×10-5 mol L−1 with a detection limit of 3.0×10-6–4.0×10-6 mol L−1. The suggested electrodes have been successfully used in the determination of ramipril drug in some pharmaceutical formulations using direct potentiometry with average recovery of >96% and mean standard deviation of <3% (n=5).